The Development and Validation of an Intercultural Business Communication Competence Scale: Evidence From Mainland China. (November 2020) - Jiao, Jing; Xu, Dejin; Zhao, Xiuqing
The aim of this article is to develop an Intercultural Business Communication Competence Scale (IBCCS) and provide evidence for the construct, convergent, discriminant, content, criterion, and external validity of the scale. The scale was developed based on 20 key elements of intercultural business communication competence (IBCC) and a review on the scales measuring international business practitioners' intercultural competence. The three factors extracted with exploratory factor analysis (EFA) were the cognitive ability for the intercultural business communication situation, business English linguistic proficiency, and intercultural business communication motivation. The scale showed sound internal consistency and the confirmatory factor analysis (CFA) demonstrated sound degree of fitness and stable scale structure. The survey results revealed that respondents' IBCC significantly correlated with their emotion intelligence (EI) and cultural intelligence (CQ). IBCCS was capable of differentiating the participants with hypothesized high IBCC level and tracking their IBCC development, which documented content validity and external validity of the measure. Hierarchical regression analysis indicated that the business students' IBCC appeared to predict their number of foreign friends and job aspiration for an international career.